Efektivitas Pesan Dakwah Terhadap Peningkatan Behaviorisme Anak - Murniati Murniati (An-Nida : Jurnal Komunikasi Islam, 2018)
The title of this research is the Effectiveness of Dakwah Message towards Increasing Child Behaviorism in learning sentra Iman Taqwa at KB PAUD Mutiara 2016. This research is aimed at finding out how far the effectiveness of Dakwah message packaged in preparing a playful environment in Sentra Iman dan Taqwa at KB Mutiara Karanggondang. The schedule of the sentra is repeated every two weeks. The method of this research is Classroom Action Research. The activity of this research is about four months. The researcher conducts two cycles in order to find out the data. The first cycle conducts on July to August. The second cycle conducts on September to October. The result of this research showed that the Dakwah message package in Sentra Iman Taqwa learning is sufficiently effective for increasing the child behaviorism.